DON MANUEL SÁNCHEZ MOLINA, PRESBÍTERO. EL MAESTRO DE PINTURA DE FRANCISCO SALZILLO - Candel Crespo, Francisco (Imafronte, 1991)
The priest Don Manuel Sánchez Molina, choir chaplain at the church of Son Bartolomé, is identified not only as Francisco Salzillo’s master of drawing, but also as painter and valuer of paintings and sculptures, what is a sign of the great prestige he had to have in his time. His religious paintings, unfortrrnately scarce nowadays, were very estimated, as his works were destinated to altarpieces by Pablo Sistori. Probably, he also cultivated portrait.